Unraveling fibrinogen-like protein 1’s role in immune regulation - Xi, Fengjia; Liu, Rongzeng (Frontiers in Immunology, 2026)
Fibrinogen-like protein 1 (FGL1) has been recently identified as an emerging novel checkpoint ligand of lymphocyte activation gene-3 (LAG-3) with important immunoregulatory functions. In addition to LAG-3, FGL1 also interacts with bone morphogenetic protein 6 (BMP6), activin receptor-like kinase 5 (ALK5) and other unidentified receptors to perform biological functions. Physiologically, FGL1 restrains intrahepatic immunity and preserves tolerance. Pathologically, FGL1 is frequently upregulated in various tumors and autoimmune diseases and is closely related to the occurrence and development of these diseases. Targeting FGL1 has shown preclinical efficacy in enhancing immunotherapy involving programmed death ligand 1 (PD-L1)/PD-1 checkpoint blockade, inhibiting liver metastasis and relieving autoimmunity without overt hepatotoxicity. In this review, we summarize recent advances in FGL1, focus on the immunoregulatory functions of FGL1, and evaluate its potential as a therapeutic target for immune-related diseases.